Measurement of the B+ total cross section and B+ differential cross section d sigma/dp(T) in p(p)over-bar collisions at root s=1.8 TeV - Acosta, D; Affolder, T; Akimoto, H; Albrow, MG; Amaral, P; Ambrose, D; Amidei, D; Anikeev, K; Antos, J; Apollinari, G; Arisawa, T; Artikov, A; et al. (2002)
We present measurements of the B+ meson total cross section and differential cross section dσ/dpT. The measurements use a 98±4 pb-1 sample of p p̄ collisions at √s=1.8 TeV collected by the CDF detector. Charged B meson candidates are reconstructed through the decay B±→J/ψK± with J/ψ→μ+μ-. The total cross section, measured in the central rapidity region |y|<1.0 for pT(B)>6.0 GeV/c, is 3.6±0.6(stat ⊕ syst) μb. The measured differential cross section is substantially larger than typical QCD predictions calculated to next-to-leading order. ©2002 The American Physical Society.